2017
DOI: 10.1016/j.heares.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of electrode discrimination with the auditory change complex in adult cochlear implant users

Abstract: The spatial auditory change complex (ACC) is a cortical response elicited by a change in place of stimulation. There is growing evidence that it provides a useful objective measure of electrode discrimination in cochlear implant (CI) users. To date, the spatial ACC has only been measured in relatively experienced CI users with one type of device. Early assessment of electrode discrimination could allow auditory stimulation to be optimized during a potentially sensitive period of auditory rehabilitation. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 58 publications
6
42
0
Order By: Relevance
“…We recently showed that it is feasible to measure the spatial ACC in different types of CI devices and as early as 1-week after switch-on in adult CI users (Mathew et al, 2017). In addition, there was a strong relationship between objective and behavioural measures of electrode discrimination.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that it is feasible to measure the spatial ACC in different types of CI devices and as early as 1-week after switch-on in adult CI users (Mathew et al, 2017). In addition, there was a strong relationship between objective and behavioural measures of electrode discrimination.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…One participant dropped out of the study after the first recording session and was therefore excluded from the analysis. Of the remaining 10 participants, 9 had taken part in our previous study (Mathew et al 2017). All participants were unilaterally implanted with an Advanced Bionics (AB) Hi-Res 90K device with full electrode array insertion and normal electrode impedances.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations